Changes in older adults' perceptions of age-friendliness in Hong Kong: A three-year mixed-methods study. (August 2022) - Chui, Cheryl Hiu-kwan; Lu, Shiyu; Chan, On Fung; Cheung, Johnson Chun-Sing; Guo, Yingqi; Liu, Yuqi; Chan, Samuel Wai; Tang, Jennifer Yee Man; Au, Alma; Wen, Zhuoyi Vincent; Yu, Ruby; Bai, Xue; et al.
Abstract: Constructing an Age-friendly City (AFC) has become a major public policy imperative in response to global population aging and urbanization. Yet there is a dearth of empirical evidence on how AFC initiatives can improve perceived age-friendliness among community-dwelling older adults, and on how such initiatives may differently affect older adults with different socioeconomic statuses. Drawing on a three-year citywide AFC initiative in Hong Kong, we conducted a trend study to evaluate changes in perceived age-friendliness in eight AFC domains with 2575 and 2697 community-dwelling older adults in 2015 and 2018 respectively, in addition to 36 focus groups involving 206 older adults. Participants were asked to share their views on changes in age-friendliness in their cities. Survey data were analyzed using linear regression while focus group data were analyzed using thematic analysis. Significant improvements were found in perceived age-friendliness in all eight AFC domains. Low-income older adults saw the greatest improvements in age-friendliness. Thematic analysis revealed that despite improvements, shortcomings persist in domains of housing, civic engagement, and employment. Nevertheless, our findings demonstrate that concerted efforts can improve a city's overall age-friendliness, and that such improvements appear most evident among low-income older adults. Highlights: A citywide Age-friendly City initiative using a bottom-up approach was implemented over a three-year period in Hong Kong. Concerted efforts from key stakeholders including nonprofit organizations, older adult ambassadors, and local governments led to significant improvements on all eight Age-friendly Cities domains. Social domains comprising respect and social inclusion, communication and information, and civic participation and employment improved the most. Improvements were greatest among low-income older adults with limited education attainment, addressing old age inequality. Incorporating older adults' views, embedding the AFC framework into urban policy and planning, and implementing continuous monitoring mechanisms are critical to constructing an AFC.